2012
DOI: 10.1111/j.1365-2621.2012.03187.x
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin content and antioxidant capacity in bran extracts of some Thai black rice varieties

Abstract: Summary This study investigated both the anthocyanin content and the antioxidant capacity of a set of genetically related glutinous and nonglutinous Thai black rice varieties. The ethanol/water extracts of the brans of these black rice varieties showed relatively potent antioxidant activities compared with those of tocopherol. These antioxidant activities were determined by thiocyanate, H2O2‐scavenging chemiluminescence (XYZ), Cu++/bathocuproine colorimetry (PAO) and 1,1‐diphenyl‐2‐picrylhydrazyl radical‐scave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 30 publications
(37 reference statements)
3
38
1
Order By: Relevance
“…The results suggested that anthocyanins had higher contribution to antioxidant properties than did phenolic compounds due to relatively high concentrations of anthocyanins compared with the overall phenolic compounds. In contrast to this study, phenolic components had higher contribution to antioxidant activity than did anthocyanin pigments (Pitija et al 2013). The contrasting results of different studies would be possibly due to materials used, evaluation methods for antioxidation, and complicated extracts containing two or more antioxidants (del Pozo-Insfran et al 2006).…”
Section: Discussioncontrasting
confidence: 99%
“…The results suggested that anthocyanins had higher contribution to antioxidant properties than did phenolic compounds due to relatively high concentrations of anthocyanins compared with the overall phenolic compounds. In contrast to this study, phenolic components had higher contribution to antioxidant activity than did anthocyanin pigments (Pitija et al 2013). The contrasting results of different studies would be possibly due to materials used, evaluation methods for antioxidation, and complicated extracts containing two or more antioxidants (del Pozo-Insfran et al 2006).…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, anthocyanin involving free radical scavenging and antioxidant is also the main phytochemical in black rice (Pitija et al, 2013). Thus, black rice would be more advantageous for medicinal property and it is also a rice genetic resource for improving rice as a functional food crop.…”
Section: Performance and Stability Of Rice Genotypesmentioning
confidence: 99%
“…In addition, black glutinous rice is a crop thought to have herbal properties and it has been used traditionally in various kinds of medical treatments. The purple pigment (anthocyanin: cyaniding-3-glucoside) in the husk (hull) and pericarp and gamma oryzanol from rice bran oil are advantageous antioxidants (Xu et al, 2001;Juliano et al, 2005;Vorarat et al, 2010;Pitija et al, 2013). Black rice contained two to three times the amount of anthocyanin and gamma oryzanol higher than did white rice (Ryu et al, 1998;Boonsit et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These compounds include anthocyanidins (cyanidin-3-O-glucoside and peonidin-3-O-glucoside [1]), flavonoids glycosides (quercetin-3-O-glucoside, isorhamnetin-3-O-glucoside and myricetin-7-O-glucoside [2]), simple phenolics (2-methoxy-4-vinylphenol (4-vinylguaiacol), 2-methoxy-phenol (guaiacol), and 1,2-benzendiol (catechol) [3]), vitamin E, (tocopherols and tocotrienols [4]), and -oryzanols (ferulate derivatives of 24-methylenecycloartenol, cycloartenol, campesterol and β-sitosterol [5]). …”
Section: Introductionmentioning
confidence: 99%